2017
DOI: 10.24873/j.rpemd.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequency analysis by the Osstell system, using the transducer screwed to different healings abutments

Abstract: a b s t r a c t a r t i c l e i n f oMethods: 60 rough surface implants were placed in 4 bovine ribs. 30 standard and 30 prototype implants were divided to group A and B, respectively. All were inserted with a torque of 30 N/ cm2, so that the rough/smooth interface was placed at bone crest level (the distance between the implants needed to be at least 4 mm). Primary stability was measured by resonance frequency analysis (RFA) with the Osstell ISQ transducer directly to the implant or over three Smartpeg screwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Other authors used this method to assess, for example, whether the height of the abutment could influence the stability values, and the results showed that the values may vary with the increase in the abutment height [27]. However, other studies have shown that varying the height of the abutments does not change the values measured by Osstell [28,29]. In our study, abutments of similar heights were used, with a difference of 1 mm between the abutments in group A and the abutments in groups B and C. However, when straight abutments were compared with angled abutments, angled abutments had lower stability values measured by RFA [27], corroborating our results.…”
Section: Plos Onementioning
confidence: 99%
“…Other authors used this method to assess, for example, whether the height of the abutment could influence the stability values, and the results showed that the values may vary with the increase in the abutment height [27]. However, other studies have shown that varying the height of the abutments does not change the values measured by Osstell [28,29]. In our study, abutments of similar heights were used, with a difference of 1 mm between the abutments in group A and the abutments in groups B and C. However, when straight abutments were compared with angled abutments, angled abutments had lower stability values measured by RFA [27], corroborating our results.…”
Section: Plos Onementioning
confidence: 99%